2024
DOI: 10.1002/ange.202403140
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorous Peptide Amphiphile with Potent Antimicrobial Activity for the Treatment of MRSA‐induced Sepsis and Chronic Wound Infection

Jingjing Hu,
Nan Liu,
Qianqian Fan
et al.

Abstract: The rising prevalence of global antibiotic resistance evokes the urgent need for novel antimicrobial candidates. Cationic lipopeptides have attracted much attention due to their strong antimicrobial activity, broad‐spectrum and low resistance tendency. Herein, a library of fluoro‐lipopeptide amphiphiles was synthesized by tagging a series of cationic oligopeptides with a fluoroalkyl tail via a disulfide spacer. Among the lipopeptide candidates, R6F bearing six arginine moieties and a fluorous tag shows the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Taken together, these results indicated that PPC induces the susceptibility of Gram-negative bacteria to phototherapy through membrane disruption, a capability in which conventional PS fails to engage. As a lipopeptide-mimic amphipathic photosensitizer, it is speculated that the hydrophilic ultrashort cation peptide RWRa of PPC first binds to the bacterial membrane due to electrostatic interactions, and then the hydrophobic AIE photosensitizer inserts into the lipid bilayer, eventually causing the physical integrity of the bacterial membrane to be disrupted by PPC. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results indicated that PPC induces the susceptibility of Gram-negative bacteria to phototherapy through membrane disruption, a capability in which conventional PS fails to engage. As a lipopeptide-mimic amphipathic photosensitizer, it is speculated that the hydrophilic ultrashort cation peptide RWRa of PPC first binds to the bacterial membrane due to electrostatic interactions, and then the hydrophobic AIE photosensitizer inserts into the lipid bilayer, eventually causing the physical integrity of the bacterial membrane to be disrupted by PPC. , …”
Section: Resultsmentioning
confidence: 99%
“…As a lipopeptide-mimic amphipathic photosensitizer, it is speculated that the hydrophilic ultrashort cation peptide RWRa of PPC first binds to the bacterial membrane due to electrostatic interactions, and then the hydrophobic AIE photosensitizer inserts into the lipid bilayer, eventually causing the physical integrity of the bacterial membrane to be disrupted by PPC. 49,50 Given the efficient disruption of the Gram-negative bacterial membrane by PPC for enhanced phototherapeutic antibacterial activity, further elucidation of the interaction sites between PPC and bacterial cell membrane was warranted. Prior to this, critical aggregation concentration (CAC) was measured and the results showed that PPC bears a CAC value of 251 μM, which was much higher than the maximum antibacterial concentration of 32 μM previously used, indicating that PPC behaves as a single molecule when acting with the OM (Figure S19, Supporting Information).…”
Section: Synthesis Andmentioning
confidence: 99%